Analysis of Decision to Work of Female Workers in Indonesia - Andi Yhudo Wijayanto; Dyah Wulan Sari (Economics Development Analysis Journal, 2019)
This study analyze the influence of demographic, social, and economic characteristics on the decision to work of female workers in Indonesia. Based on the data of the National Labor Force Survey (Sakernas) August 2017, this study is conducted by using multinomial logistic regression method to achieve the objective. The result shows the characteristics of demographic, social, and economic have significant effect on the decision to work of female workers in Indonesia. Female workers tend to work in tertiary sector than primary sector. This finding is in line with the trend of increasing female workers in the tertiary sector which is one of the factor that influence the shift in economic structure in Indonesia. Another finding is that the increase of wage reduce the probability of female workers to work in the secondary sector. This condition is probably related to the existence of rules of minimum wage and work contract which bind female workers in the secondary sector, especially in large and medium industrial sector.